Enhancing cardiorespiratory and muscular endurance in football players: The impact of a six-week interval training program - Singh, Laishram Santosh; Farooque, Sm; Singh, Waribam James; Zelenovic, Milan (UIR Press, 2024)
Background Problem: The integration of interval training programs has emerged as a focal point for enhancing the cardiorespiratory endurance and muscular endurance of players. Research Objectives: The main purpose of the present study is to investigate the effect of interval training program on cardiorespiratory endurance and muscular endurance of football payers. Methods: A total of thirty male football players (age 18-24 year) were selected from Imphal West District, Imphal, Manipur (India) who participated in the national level competition. The subjects were randomly assigned into two equal groups, experimental group (n = 15) and control group (n = 15). Before the intervention featuring a six-week interval training program five days of sessions per week (Monday to Friday) each lasting 60 minutes, groups underwent initial assessments through which Cooper’s 12-minute run/walk test for cardiorespiratory endurance and bent-knee sit-ups for muscular endurance. Pre and post-test scores underwent statistical analysis, utilizing descriptive statistics and the Analysis of Covariance test (ANCOVA). The level of significance was set at 0.05 level of confidence. Findings and Results: The experimental group showed improved scores in the cardiorespiratory endurance and muscular endurance compared to the control group (p < 0.05). The mean of the cardiorespiratory endurance and muscular endurance for pretest and posttest of the experimental group were 25.68 ± 25.85 and 27.82 ± 26.25 respectively. The mean of the cardiorespiratory endurance and muscular endurance for pre-test and post-test of the control group were 28.24 ± 28.42 and 32.58 ± 28.80 respectively. Conclusion: It was concluded that the interval training program group had shown significantly improved cardiorespiratory endurance and muscular endurance and the control group had insignificant improvement. It was confirmed that a six weeks interval training program was effective to improve the cardiorespiratory endurance and muscular endurance of football players.